The clinical course of critical limb ischaemia and the role of endovascular revascularisation in patients with diabetes - Olga Nikolaevna Bondarenko (Endocrinology Research Centre, 2015)
Recent data suggest that chronic critical limb ischaemia (CLI) is the most important reason for amputation among diabetic patients. The high prevalence of CLI in this patient group is associated with specific clinical and morphological properties of peripheral arterial disease. Percutaneous transluminal angioplasty is an appropriate primary therapy, but it is not considered early in the disease process, and is instead reserved as a limb salvage strategy. Low primary patency, despite optimal clinical effects, remains a typical issue of percutaneous transluminal angioplasty for diabetic patients in particular. Thus, the indications, technical success and clinical results of endovascular revascularisation need to be clarified in patients with diabetes. Although difficult, the procedure can be effective through a multidisciplinary approach.